Fiscalização do Contrato de Gestão de Serviços de Saúde no Hospital Estadual Central - Assis, Bethânia Alves de (2019)
The economic and financial openness that occurred in Brazil in the 1990s and the competitive scenario of the time allowed companies to make changes in work organization and management processes and to adopt outsourcing as a cost reduction strategy and sea